Brand new medicament and process for efficiently repairing reverse osmosis membrane

By constructing a composite membrane structure of nano self-healing particles and anti-fouling polymer materials on the reverse osmosis membrane, the problem of membrane susceptibility to contamination is solved, and efficient anti-fouling performance and long life are achieved. It is suitable for a variety of water treatment scenarios .

CN119281130APending Publication Date: 2025-01-10广东粤电靖海发电有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411645168.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing reverse osmosis membranes are susceptible to pollutants such as organic matter, microorganisms and colloids during long-term operation, resulting in poor anti-fouling performance and short service life.

Method used

Nano-self-healing particles and anti-fouling polymer materials are used to form a composite membrane structure. The nano-self-healing particles are made of nanosilver or nano-zinc oxide. After surface modification, polyethylene glycol or polytetrade of anti-fouling polymer materials are made of Vinyl fluoride forms a low surface energy anti-fouling layer and constructs a nano-self-healing layer and anti-fouling polymer film layer through specific process steps.

Benefits of technology

It significantly improves the anti-fouling performance of the membrane, extends the service life, maintains high water flux and separation performance, reduces operating costs, and automatically adjusts self-healing behavior under different environmental conditions, which is suitable for a wider range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281130A_ABST
    Figure CN119281130A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membrane separation, and discloses a brand new medicament for efficiently repairing a reverse osmosis membrane, the brand new medicament comprises nano self-healing particles and an anti-fouling polymer which are used for constructing a composite membrane, the composite membrane comprises a base membrane layer, an anti-fouling polymer membrane layer and a nano self-healing layer, the nano self-healing particles are selected from nano-silver or nano-zinc oxide particles, and the anti-fouling polymer membrane layer is selected from nano-silver or nano-zinc oxide particles. Carrying out surface modification; the anti-fouling polymer material is selected from polyethylene glycol or polytetrafluoroethylene and forms an anti-fouling layer with low surface energy; the surface modification of the nano self-healing particles adopts a silane coupling agent for treatment. The anti-fouling polymer membrane layer is added on the base membrane layer, the anti-fouling polymer membrane layer has good hydrophilicity and low surface energy, adsorption and deposition of pollutants on the surface of the membrane can be effectively reduced, high water flux and separation performance of the membrane are maintained by reducing accumulation of the pollutants on the surface of the membrane, the cleaning period is prolonged, and performance degradation caused by pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane separation technology, in particular to a new agent and process for efficiently repairing a reverse osmosis membrane. Background Art

[0002] As an efficient means of water treatment and separation, reverse osmosis membrane technology has been widely used in seawater desalination, industrial wastewater treatment, drinking water purification and other fields. With the increasing global water shortage and environmental pollution problems, the demand for high-performance reverse osmosis membranes continues to grow. In order to meet this demand, the development of a new agent and process that can efficiently repair reverse osmosis membranes has important practical significance and application value.

[0003] At present, reverse osmosis membranes usually adopt a thin film composite structure, which is composed of a polyamide active layer, a microporous support layer and a non-woven fabric substrate. Its working principle is to use a semi-permeable membrane under external pressure to allow water molecules to pass through the membrane and intercept soluble salts and other impurities to achieve water purification and separation. In order to improve the performance of the membrane, the prior art often uses surface modification, material improvement and structural optimization to improve the flux, selectivity and mechanical strength of the membrane. For example, the membrane surface is modified by chemical coating or plasma treatment to enhance its hydrophilicity or anti-pollution ability.

[0004] However, the existing reverse osmosis membranes are susceptible to pollutants such as organic matter, microorganisms and colloids during long-term operation, resulting in contamination and clogging of the membrane surface. This contamination will significantly reduce the water permeability of the membrane, increase operating pressure and energy consumption, and shorten the service life of the membrane. Although there are some anti-pollution technologies, such as adding hydrophilic groups or antibacterial agents to the membrane surface, the effect is still not ideal and the problem of membrane contamination cannot be fundamentally solved. Therefore, how to effectively improve the anti-fouling performance of reverse osmosis membranes has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a new agent and process for efficiently repairing reverse osmosis membranes, which solves the problem that the existing reverse osmosis membranes are easily affected by pollutants, resulting in poor anti-fouling performance and short service life.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a new agent for efficiently repairing reverse osmosis membranes, comprising nano self-healing particles and anti-fouling polymers for constructing a composite membrane, wherein the composite membrane comprises a base membrane layer, an anti-fouling polymer membrane layer and a nano self-healing layer, characterized in that: the nano self-healing particles are selected from nano silver or nano zinc oxide particles, and are surface modified; The anti-fouling polymer material is selected from polyethylene glycol or polytetrafluoroethylene to form an anti-fouling layer with low surface energy.

[0007] Preferably, the surface modification of the nano self-healing particles is carried out by treatment with a silane coupling agent.

[0008] Preferably, the nano self-healing particles are temperature responsive or pH responsive, including the following: The temperature responsiveness is achieved by incorporating a thermosensitive polymer into the particles; The pH responsiveness is achieved by incorporating pH sensitive materials into the particles.

[0009] Preferably, the anti-fouling polymer film layer has a thickness ranging from 5 to 10 micrometers, and the nano self-healing layer has a thickness ranging from 30 to 50 nanometers.

[0010] Preferably, the base film layer has a thickness ranging from 50 to 100 microns, and the base film layer is made of polyamide material and is formed by heat treatment at 100°C.

[0011] The new preparation process of the reagent for efficiently repairing the reverse osmosis membrane includes the following steps: dissolving polyamide in N,N-dimethylformamide solvent to form a base film layer solution; Dissolving or dispersing polyethylene glycol or polytetrafluoroethylene to form an antifouling polymer solution, and coating the solution on the base film layer by dipping to form an antifouling film layer; The surface-modified nano self-healing particles are dispersed in ethanol or aqueous solution, a polyvinyl alcohol film-forming agent is added and coated on the anti-fouling film layer to form a nano self-healing layer.

[0012] Preferably, the steps of preparing the base film layer include: The polyamide solution was evenly coated on the glass plate by knife coating; Pre-drying is performed at 40°C and heat treatment is performed at 100°C for 20 minutes to cure and form a base film layer.

[0013] Preferably, the steps of preparing the antifouling polymer film layer include: The antifouling polymer solution was prepared by dispersing PTFE in ethanol by ultrasonic dispersion; The base film layer is immersed in the antifouling polymer solution for 3 to 5 minutes by dip coating, and UV curing or 80°C thermal curing is adopted to form an antifouling layer.

[0014] Preferably, the steps of preparing the nano self-healing layer include: Performing surface modification treatment on nano silver or nano zinc oxide particles with a silane coupling agent to control the particle size to be between 20 and 30 nanometers; The modified nanoparticles are dispersed in ethanol or aqueous solution, and a polyvinyl alcohol film-forming agent is added, and the nanoparticles are coated on the antifouling polymer film layer by spin coating at a rate of 2000 rpm for 30 seconds.

[0015] Preferably, after coating, the nano self-healing layer is low-temperature cured at 50° C. for 30 minutes to allow the film-forming agent to stably adhere to the anti-fouling polymer film layer.

[0016] The present invention provides a new agent and process for efficiently repairing reverse osmosis membranes. It has the following beneficial effects: 1. The present invention adds an anti-fouling polymer membrane layer, such as polyethylene glycol, on the base membrane layer. This layer has good hydrophilicity and low surface energy, and can effectively reduce the adsorption and deposition of pollutants on the membrane surface. By reducing the accumulation of pollutants on the membrane surface, the high water flux and separation performance of the membrane are maintained, the cleaning cycle is extended, and the performance degradation caused by pollution is reduced.

[0017] 2. The present invention enables the membrane to automatically repair itself when it is microscopically mechanically damaged by coating the membrane surface with a nano self-healing layer, such as a coating containing nano silver. The nano self-healing particles are activated when the temperature or pH changes, filling the micro cracks on the membrane surface and restoring the integrity of the membrane. This self-healing ability significantly extends the service life of the membrane and reduces the frequency of replacement due to membrane damage.

[0018] 3. After multiple pollution-cleaning cycles, the performance retention rate of the composite membrane of the present invention is higher than 95%, showing excellent durability. This is due to the protection of the anti-fouling layer and the repair effect of the self-healing layer, which enables the membrane to maintain stable water permeability and separation performance in long-term operation, reducing operating costs and improving the overall efficiency of the water treatment system.

[0019] 4. The present invention introduces temperature and pH responsive materials, so that the membrane can automatically adjust the self-healing behavior under different environmental conditions. Under high temperature or acid-base conditions, the responsive materials are activated, which enhances the self-healing effect and makes the membrane suitable for a wider range of application scenarios, such as high-temperature wastewater treatment or acid-base sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1: Please see attached Figure 1 The embodiment of the present invention provides a new agent and process for efficiently repairing a reverse osmosis membrane, including: Step 1: Preparation of base film layer In this embodiment, the base membrane layer is made of polyamide (PA) material, which provides the main separation function and mechanical support of the reverse osmosis membrane.

[0023] (1) Preparation of polyamide solution Material: Polyamide (PA) powder, molecular weight about 10,000 g / mol, guaranteed purity above 99%.

[0024] N,N-dimethylformamide (DMF) solvent, analytical grade, water content less than 0.1%.

[0025] step: Weighing: Weigh 10 g of polyamide powder using an electronic balance with an accuracy of 0.01 g.

[0026] Dissolution: Add 90 ml of DMF solvent to a 250 ml beaker and place it on a magnetic stirrer.

[0027] Add PA: Gradually add polyamide powder into DMF solvent slowly with a stirring speed of 500 rpm to prevent powder agglomeration.

[0028] Stirring and dissolving: Continue stirring at 25°C for 2 hours until the polyamide is completely dissolved to form a uniform polyamide solution with a concentration of 10wt%.

[0029] (2) Preparation of basement membrane equipment: The glass plate, with a size of 30 cm × 30 cm, was cleaned with anhydrous ethanol and dried for later use.

[0030] Knife coating unit, the applicator gap was set to 200 microns.

[0031] step: Coating: Pour the polyamide solution on one end of the glass plate and use a knife coating device to evenly coat the solution on the glass plate at a speed of 5 cm / s to ensure uniform film thickness.

[0032] Pre-drying: Place the coated glass plate in a 40°C oven for 30 minutes to evaporate the solvent and initially form a film layer.

[0033] (3) Heat treatment and film formation step: Heat treatment: The temperature of the pre-dried membrane was gradually raised to 80 °C in an oven and maintained for 1 h to further remove the solvent and promote membrane densification.

[0034] Cooling and demoulding: The film was cooled naturally to room temperature (about 25°C), and then a plastic scraper was used to gently pry up a corner of the film at the edge of the glass plate to evenly peel the film from the glass plate to obtain a self-supporting polyamide-based film.

[0035] Logical relationship: By controlling the coating thickness and heat treatment conditions, a base membrane with uniform pore size and good mechanical strength is obtained, providing a stable foundation for subsequent film coating.

[0036] Step 2: Coating of antifouling polymer film In this embodiment, the anti-fouling polymer film layer is coated on the surface of the base film using polyethylene glycol (PEG) to reduce the adsorption of pollutants on the membrane surface.

[0037] (1) Preparation of PEG solution Material: Polyethylene glycol (PEG-4000), molecular weight about 4000, purity 99%.

[0038] Deionized water, conductivity less than 0.1 μS / cm.

[0039] step: Weighing: Weigh 2 g of PEG-4000.

[0040] Dissolution: Add PEG-4000 to 100 mL of deionized water, place in a 60°C water bath, and stir for 30 minutes until completely dissolved to form a 2 wt% PEG solution.

[0041] (2) Coating of anti-fouling layer step: Dip coating: The prepared base membrane was vertically immersed in the PEG solution for 5 min to ensure that PEG fully penetrated and adsorbed on the membrane surface.

[0042] Pull-drying: The membrane was slowly pulled at a speed of 1 mm / s, and hung at room temperature for 30 minutes to allow the water to evaporate naturally and form a uniform coating of PEG on the membrane surface.

[0043] Logical relationship: Through impregnation and slow pulling, the uniformity and density of the anti-fouling layer are ensured; natural drying avoids membrane deformation and structural damage caused by thermal stress.

[0044] (3) Curing treatment step: UV curing: The dried film was placed in a UV curing box and irradiated with a UV lamp with a wavelength of 365 nm for 10 minutes to promote cross-linking between PEG molecules and improve the stability and durability of the coating.

[0045] Logical relationship: UV curing enhances the adhesion and stability of the PEG layer, preventing the PEG layer from being dissolved by water or mechanically peeled off during use.

[0046] Step 3: Preparation and coating of nano self-healing layer In this embodiment, the nano self-healing layer is realized by coating nano silver (Ag) particles on the surface of the membrane. Nano silver has self-healing and antibacterial properties.

[0047] (1) Preparation and surface modification of silver nanoparticles Material: Nanosilver particles have an average particle size of about 20 nanometers and a purity of 99.9%.

[0048] 3-Aminopropyltriethoxysilane (APTES) was of analytical grade.

[0049] Anhydrous ethanol, analytical grade.

[0050] step: Weighing: Weigh 0.5 g of nanosilver particles.

[0051] Dispersion: Add the nanosilver particles into 50 ml of anhydrous ethanol and use an ultrasonic cleaner to ultrasonically disperse them for 30 minutes to make the particles evenly suspended.

[0052] Surface modification: 0.5 ml of APTES was added to the nanosilver ethanol dispersion and stirring was continued for 2 h to complete the surface modification and enhance the binding force between the nanosilver particles and the PEG coating.

[0053] Logical relationship: Surface modification gives the surface of nanosilver particles amino functional groups, which can form hydrogen bonds or chemical bonds with the hydroxyl groups in PEG, thereby enhancing the adhesion of the particles and preventing them from falling off during use.

[0054] (2) Preparation of nano self-healing coating Material: Polyvinyl alcohol (PVA), molecular weight 88,000, partially hydrolyzed.

[0055] step: Solution preparation: Add 1 gram of PVA to 50 ml of the modified nanosilver ethanol solution and stir for 1 hour until it is completely dissolved to form a nanosilver-PVA coating solution.

[0056] Spin coating: Fix the membrane on the spin coater, add 2 ml of nanosilver-PVA coating solution, set the spin coating speed to 2000 rpm, and spin coat for 30 seconds to form a uniform nano self-healing layer.

[0057] Logical relationship: PVA, as a film-forming agent, helps nanosilver particles form a dense coating on the membrane surface; the spin coating method ensures that the coating thickness is controllable, usually around 50 nanometers, to avoid adverse effects on the water permeability of the membrane.

[0058] (3) Low temperature curing step: Curing treatment: The film coated with the nano self-healing layer was placed in an oven at 50°C and dried for 1 hour to evaporate the ethanol and water, solidify the PVA, and firmly embed the nanosilver particles into the coating.

[0059] Logical relationship: Low-temperature curing prevents the influence of high temperature on the base film and anti-fouling layer, ensures the stability of the membrane structure, and at the same time fully cures the PVA to enhance the mechanical strength and water resistance of the coating.

[0060] Step 4: Introducing temperature and pH responsive materials In this embodiment, in order to enhance the function of the self-healing layer, temperature-sensitive and pH-sensitive materials are added to enable the membrane to have adaptive self-healing capabilities under different environmental conditions.

[0061] (1) Addition of thermosensitive polymer Material: Poly(N-isopropylacrylamide) (PNIPAM), purity 99%.

[0062] step: Solution preparation: Add 0.5 g of PNIPAM to the nanosilver-PVA coating solution and stir for 1 hour until it is completely dissolved.

[0063] Coating: Following the previous spin coating step, a layer of PNIPAM-containing coating was applied to the membrane surface again at a spin coating speed of 2000 rpm for 30 seconds.

[0064] Logical relationship: PNIPAM will undergo a phase change above 32°C, changing from hydrophilic to hydrophobic, and aggregate on the membrane surface, promoting the movement of nanosilver particles, filling the microcracks on the membrane surface, and improving the self-healing ability under high temperature conditions.

[0065] (2) Addition of pH sensitive materials Material: Chitosan, deacetylation degree over 80%, purity 99%.

[0066] step: Solution preparation: Dissolve 0.5 g of chitosan in 50 ml of 1% (volume fraction) acetic acid solution and stir for 2 hours until completely dissolved.

[0067] Coating: Use the spraying method to evenly spray the chitosan solution on the membrane surface and dry it at room temperature for 2 hours to form a thin layer.

[0068] Chitosan is soluble under acidic conditions and precipitates under alkaline conditions. It can undergo dissolution-precipitation conversion in different pH environments and promote self-healing of the membrane surface.

[0069] Step 5: Membrane performance testing and process optimization In this embodiment, a number of performance tests are performed on the prepared composite membrane to verify its performance and to perform process optimization when necessary.

[0070] (1) Water permeability test step: Install the membrane: Cut the membrane into discs with a diameter of 75 mm and install them in the flat-plate reverse osmosis test device to ensure a good seal.

[0071] Test conditions: operating pressure of 1.5 MPa, inlet water containing 1000 mg / L NaCl, temperature of 25°C.

[0072] Data recording: After 30 minutes of stable operation, the volume of the permeate was measured and the water flux (L / m²·h) and salt retention rate (%) were calculated.

[0073] result: The water flux reaches 250 L / m²·h.

[0074] The salt retention rate reaches over 95%.

[0075] Logical relationship: The water permeability test verifies the separation performance of the membrane and ensures that the various layers of the composite membrane will not adversely affect the permeability of the base membrane.

[0076] (2) Anti-fouling performance test step: Fouling simulation: 1 g / L bovine serum albumin (BSA) solution was used as the simulated fouling.

[0077] Test process: Add 2 ml of BSA solution on the membrane surface, let it stand for 1 hour, and then rinse the membrane surface with pure water.

[0078] Water flux measurement: Measure the water flux of the membrane again and compare the changes in water flux before and after pollution.

[0079] Result analysis: The water flux decreased by less than 5%, indicating that the membrane had good anti-fouling performance.

[0080] Logical relationship: The anti-fouling performance test verifies the effectiveness of the anti-fouling layer, ensuring that the membrane is not easily clogged by pollutants during long-term operation, thereby reducing the cleaning frequency.

[0081] (3) Self-healing performance test Scratch test: Use a scratch tester to make a scratch with a width of 10 μm and a length of about 1 cm on the film surface.

[0082] Self-healing process: The membrane was placed in a water bath at 40°C for 2 h.

[0083] Observation of results: The scratch repair was observed using an optical microscope or a scanning electron microscope (SEM).

[0084] The scratches basically disappeared, indicating that the self-healing rate exceeded 90%.

[0085] Logical relationship: The self-healing performance test verifies the synergistic effect of the nano self-healing layer and the temperature-sensitive material. The membrane can effectively repair micro-damage under high temperature conditions and improve its service life.

[0086] (4) Self-healing test under pH conditions step: Acid-base treatment: The scratched membrane was immersed in buffer solutions of pH = 4 and pH = 10, respectively, and allowed to stand for 2 hours.

[0087] Observation results: The scratch repair was also observed using a microscope.

[0088] Under different pH conditions, the scratches were obviously repaired, proving the effectiveness of pH-sensitive materials.

[0089] Logical relationship: The introduction of pH-sensitive materials enables the membrane to achieve self-healing in acidic or alkaline environments, expanding the scope of application of the membrane.

[0090] (5) Durability test step: Cycle test: The membrane was subjected to 10 fouling-cleaning cycles, each time fouled with BSA solution and then cleaned with 0.1wt% NaOH solution to simulate the cleaning process in actual use.

[0091] Performance evaluation: After each cycle, the water flux and salt rejection of the membrane were measured and the data were recorded.

[0092] Data analysis: Compare initial performance and performance changes after cycling.

[0093] result: After 10 cycles, there was no significant decrease in water flux and salt retention rate, the membrane performance was stable, and the performance retention rate was above 95%.

[0094] Logical relationship: Durability testing proves the stability of the membrane during long-term use and cleaning, meeting the needs of industrial applications and reducing the frequency of membrane replacement and operating costs.

[0095] Embodiment 2: In this Example 2, the material of the antifouling polymer membrane layer is changed from polyethylene glycol (PEG) to polyvinylidene fluoride (PVDF). The other steps and materials are consistent with Example 1. The purpose is to investigate the effect of different antifouling materials on the performance of the composite membrane and prove that the use of PEG as the antifouling layer material in Example 1 is more effective.

[0096] Step 1: Preparation of base film layer Same as the first embodiment.

[0097] Material: Polyamide (PA) powder, molecular weight about 10,000 g / mol, purity more than 99%.

[0098] N,N-Dimethylformamide (DMF) solvent was of analytical grade.

[0099] step: 10 g of polyamide powder was weighed, dissolved in 90 ml of DMF solvent, and stirred for 2 hours to form a 10 wt % polyamide solution.

[0100] Coating: The polyamide solution was evenly coated on the glass plate using a knife coating method with the gap set to 200 μm.

[0101] Pre-drying: Pre-dry at 40°C for 30 minutes.

[0102] Heat treatment: Heat treatment at 80°C for 1 hour, demoulding after cooling, and obtaining a base film layer.

[0103] Step 2: Coating of antifouling polymer film In the second embodiment, the antifouling polymer membrane layer uses polyvinylidene fluoride (PVDF) instead of PEG to evaluate the effects of different antifouling materials on membrane performance.

[0104] (1) Preparation of PVDF solution Material: Polyvinylidene fluoride (PVDF) powder, molecular weight about 275,000 g / mol, purity 99%.

[0105] N,N-Dimethylacetamide (DMAc) solvent was analytical grade.

[0106] step: Weigh 10 g of PVDF powder.

[0107] Dissolution: Add PVDF powder to 90 ml of DMAc solvent, place in an oil bath at 60°C, and stir for 6 hours to form a 10 wt% PVDF solution.

[0108] (2) Coating of anti-fouling layer step: Coating: Spread the base film layer flat on the applicator, and use the knife coating method to evenly coat the PVDF solution on the surface of the base film, with the gap set to 100 microns.

[0109] Drying: The coated film was placed in an oven at 60°C for 2 hours to remove the solvent and form a PVDF antifouling layer.

[0110] (3) Curing treatment step: Heat treatment: The membrane was heat treated at 80 °C for 1 h to enhance the crystallinity and stability of the PVDF layer.

[0111] Logical relationship: PVDF has good chemical stability and hydrophobicity, and as an anti-fouling layer, it can reduce the adsorption of pollutants on the membrane surface. However, compared with PEG, PVDF has poorer hydrophilicity, which may affect the water permeability and anti-fouling performance of the membrane.

[0112] Step 3: Preparation and coating of nano self-healing layer Same as the first embodiment.

[0113] Material: Nanosilver particles, average particle size 20 nanometers, purity 99.9%.

[0114] 3-Aminopropyltriethoxysilane (APTES).

[0115] Anhydrous ethanol.

[0116] Polyvinyl alcohol (PVA).

[0117] Poly(N-isopropylacrylamide) (PNIPAM).

[0118] Chitosan.

[0119] step: Surface modification of nanosilver particles: react with APTES in anhydrous ethanol and ultrasonically disperse to complete the surface modification.

[0120] Preparation of nano self-healing coating: Modified nano silver particles, PVA and PNIPAM are mixed to prepare a coating liquid.

[0121] Spin coating: Spin-coat the nano self-healing coating on the PVDF anti-fouling layer at a speed of 2000 rpm for 30 seconds.

[0122] Low-temperature curing: Dry at 50°C for 1 hour to complete the preparation of the nano self-healing layer.

[0123] Logical relationship: The preparation method of the nano self-healing layer is consistent with that of Example 1, ensuring that the only variable is the change in the anti-fouling polymer film layer material.

[0124] Step 4: Introducing temperature and pH responsive materials Same as the first embodiment.

[0125] Thermosensitive polymer: Add PNIPAM to improve the self-healing ability under high temperature conditions.

[0126] pH sensitive material: Spraying chitosan solution gives the membrane self-healing properties under different pH conditions Step 5: Membrane performance testing and process optimization (1) Water permeability test Test conditions: Same as those in Example 1.

[0127] result: Water flux: 200 L / m²·h.

[0128] Salt retention rate: 93%.

[0129] Analysis: Compared with Example 1, the water flux decreased and the salt retention rate slightly decreased, which may be related to the increase in water permeability resistance caused by the hydrophobicity of the PVDF anti-fouling layer.

[0130] (2) Anti-fouling performance test Test method: Same as that in Example 1.

[0131] result: The water flux decreased by about 15%, indicating that the anti-fouling performance of the membrane was lower than that of Example 1.

[0132] Analysis: The hydrophobicity of PVDF makes it easier for pollutants to adsorb on the membrane surface, reducing the anti-fouling performance.

[0133] (3) Self-healing performance test Test method: Same as that in Example 1.

[0134] result: The scratch repair rate is about 70%.

[0135] Analysis: The hydrophobicity of the PVDF anti-fouling layer may affect the functionality of PNIPAM and chitosan in the nano self-healing layer, reducing the self-healing efficiency.

[0136] (4) Durability test Test method: Same as that in Example 1.

[0137] result: After 10 cycles, the water flux and salt rejection decreased by about 15%.

[0138] Analysis: The durability of the membrane is worse than that of Example 1, which may be due to the decrease in anti-fouling performance and self-healing performance, resulting in membrane fouling and damage accumulation.

[0139] Embodiment three: In this Example 3, the nanoparticles of the nano self-healing layer are changed from nano silver (Ag) to nano titanium dioxide (TiO2). The other steps and materials are consistent with Example 1. The purpose is to investigate the effects of different nano self-healing particles on the performance of the composite film and prove that the effect of using nano silver as the self-healing particles in Example 1 is better.

[0140] Step 1: Preparation of base film layer Same as the first embodiment.

[0141] Material: Polyamide (PA) powder, molecular weight about 10,000 g / mol, purity more than 99%.

[0142] N,N-Dimethylformamide (DMF) solvent was of analytical grade.

[0143] step: 10 g of polyamide powder was weighed, dissolved in 90 ml of DMF solvent, and stirred for 2 hours to form a 10 wt % polyamide solution.

[0144] Coating: The polyamide solution was evenly coated on the glass plate using a knife coating method with the gap set to 200 μm.

[0145] Pre-drying: Pre-dry at 40°C for 30 minutes.

[0146] Heat treatment: Heat treatment at 80°C for 1 hour, demoulding after cooling, and obtaining a base film layer.

[0147] Step 2: Coating of antifouling polymer film Same as the first embodiment.

[0148] Material: Polyethylene glycol (PEG-4000), molecular weight about 4000, purity 99%.

[0149] Deionized water.

[0150] step: Weigh 2 g of PEG-4000, dissolve it in 100 ml of deionized water, and stir at 60 °C for 30 min to form a 2 wt % PEG solution.

[0151] Dip coating: vertically immerse the basement membrane in the PEG solution for 5 minutes.

[0152] Pull-drying: The film was slowly pulled at a speed of 1 mm / s and dried at room temperature for 30 minutes.

[0153] UV curing: In a UV curing box, irradiate at 365 nm for 10 minutes.

[0154] Step 3: Preparation and coating of nano self-healing layer In the third embodiment, the nanoparticles of the nano self-healing layer are changed from nanosilver (Ag) to nanotitanium dioxide (TiO2) to evaluate the effects of different nanoparticles on the self-healing performance.

[0155] (1) Preparation and surface modification of nano-titanium dioxide particles Material: Nano titanium dioxide (TiO2) particles, with an average particle size of about 20 nanometers and a purity of 99.9%.

[0156] 3-Aminopropyltriethoxysilane (APTES).

[0157] Anhydrous ethanol.

[0158] step: Weigh 0.5 g of nano-TiO2 particles.

[0159] Dispersion: Add nano-TiO2 particles into 50 ml of anhydrous ethanol and disperse them by ultrasonic for 30 minutes.

[0160] Surface modification: 0.5 ml of APTES was added to the nano-TiO2 ethanol dispersion and stirred for 2 hours to complete the surface modification.

[0161] (2) Preparation of nano self-healing coating Material: Polyvinyl alcohol (PVA).

[0162] Poly(N-isopropylacrylamide) (PNIPAM).

[0163] Chitosan.

[0164] step: Solution preparation: Add 1 g of PVA and 0.5 g of PNIPAM to 50 ml of the modified nano-TiO2 ethanol solution and stir for 1 hour.

[0165] Spin coating: add the coating liquid dropwise onto the antifouling PEG layer at a spin coating speed of 2000 rpm for 30 seconds to form a nano self-healing layer.

[0166] Low temperature cure: dry at 50°C for 1 hour.

[0167] (3) Spraying of pH sensitive materials step: Chitosan solution: As in Example 1, 0.5 g of chitosan was dissolved in 50 ml of 1% acetic acid solution.

[0168] Spraying: Spray chitosan solution evenly on the membrane surface and dry at room temperature for 2 hours.

[0169] Logical relationship: Nano-TiO2 has certain self-healing and photocatalytic properties, but its effect may be different from that of nano-silver. By comparing with Example 1, the applicability of nano-TiO2 in the self-healing layer is evaluated.

[0170] Step 4: Introducing temperature and pH responsive materials Same as the first embodiment.

[0171] Thermosensitive polymer: PNIPAM has been incorporated into nano self-healing coatings.

[0172] pH sensitive material: Chitosan has been sprayed on the membrane surface.

[0173] Step 5: Membrane performance testing and process optimization (1) Water permeability test Test conditions: Same as those in Example 1.

[0174] result: Water flux: 240 L / m²·h.

[0175] Salt retention rate: 94%.

[0176] Analysis: The water flux is slightly lower than that in Example 1, and the salt retention rate is also reduced, which may be related to the fact that the surface properties of nano-TiO2 affect the separation performance of the membrane.

[0177] (2) Anti-fouling performance test Test method: Same as that in Example 1.

[0178] result: The water flux decreased by about 7%, and the anti-fouling performance was slightly inferior to that of Example 1.

[0179] Analysis: The hydrophilicity of nano-TiO2 may be slightly lower than that of nano-silver, which has a certain impact on the anti-fouling performance.

[0180] (3) Self-healing performance test Test method: Same as that in Example 1.

[0181] result: The scratch repair rate is about 80%.

[0182] Analysis: The self-healing performance of nano-TiO2 is not as good as that of nano-silver, probably due to its lower activity in temperature- and pH-responsive materials.

[0183] (4) Durability test Test method: Same as that in Example 1.

[0184] result: After 10 cycles, the water flux and salt retention rate decreased by about 10%.

[0185] Analysis: The durability of the membrane is slightly worse than that of Example 1, but better than that of Example 2.

[0186] Table 1 is a comparison table of experimental data of the embodiment.

[0187] Embodiment 1 Embodiment 2 Embodiment 3 Antifouling polymer membrane materials Polyethylene glycol Polyvinylidene fluoride Polyethylene glycol Nano self-healing particle materials Nano Silver Nano Silver Nano Titanium Dioxide Water flux (L / m²·h) 250 200 240 Salt retention rate (%) 95 93 94 Antifouling performance (water flux reduction, %) <5 ≈15 ≈7 Self-healing rate (%) >90 ≈70 ≈80 Durability (performance retention after 10 cycles, %) >95 ≈85 ≈90 By comparing the above experimental data, it can be clearly seen that: The first embodiment is superior to the second and third embodiments in terms of key performance indicators such as water flux, salt retention rate, anti-fouling performance, self-healing rate and durability.

[0188] In Example 2, due to the change of the anti-fouling polymer membrane material to PVDF, the water permeability, anti-fouling performance and self-healing performance were all reduced.

[0189] Although the anti-fouling polymer film material of the third embodiment is the same as that of the first embodiment, the nano self-healing particle material is replaced with nano-TiO2, which results in a decrease in the self-healing performance and durability.

[0190] Conclusion: The technical solution of Example 1 achieves the best membrane performance by using polyethylene glycol (PEG) as the anti-fouling polymer membrane material and nanosilver (Ag) as the nano self-healing particle material, which proves the effectiveness and superiority of the present invention.

[0191] Comparative Example: In this comparative example, a conventional reverse osmosis membrane preparation method was used, and no antifouling polymer membrane layer and nano self-healing layer were used, and only a pure polyamide reverse osmosis membrane was prepared. By comparing the data with those of Example 1, the improvement effect of the technical solution of the present invention over the conventional method was evaluated.

[0192] Step 1: Preparation of base film layer Similar to Example 1, a polyamide (PA) base film layer was prepared.

[0193] Material: Polyamide (PA) powder, molecular weight about 10,000 g / mol, purity more than 99%.

[0194] N,N-Dimethylformamide (DMF) solvent was of analytical grade.

[0195] step: 10 g of polyamide powder was weighed, dissolved in 90 ml of DMF solvent, and stirred for 2 hours to form a 10 wt % polyamide solution.

[0196] Coating: Use knife coating to evenly coat the polyamide solution on a clean glass plate with a gap set to 200 μm.

[0197] Pre-drying: Pre-dry at 40°C for 30 minutes to partially remove the solvent.

[0198] Heat treatment: Heat treatment at 80°C for 1 hour to fully cure the film.

[0199] Cooling and demoulding: Cool to room temperature, gently peel off the membrane layer to obtain pure polyamide reverse osmosis membrane.

[0200] Logical relationship: Since no anti-fouling layer and self-healing layer are used, the base membrane layer directly serves as the final reverse osmosis membrane, which has higher permeability and separation performance, but is susceptible to pollution and damage.

[0201] Step 2: Membrane performance test (1) Water permeability test Test conditions: Operating pressure: 1.5 MPa.

[0202] Influent: aqueous solution containing 1000 mg / L NaCl.

[0203] Temperature: 25°C.

[0204] result: Water flux: 280 L / m²·h.

[0205] Salt retention rate: 96%.

[0206] Analysis: Pure polyamide membrane has high water flux and salt rejection, and good initial performance.

[0207] (2) Anti-fouling performance test Test method: Same as in Example 1, using 1 g / L bovine serum albumin (BSA) solution as simulated dirt.

[0208] result: The water flux dropped by about 25%, indicating that the membrane performance decreased significantly after fouling.

[0209] Analysis: Traditional membranes lack an anti-fouling layer and are easily clogged by pollutants, resulting in a significant drop in water flux.

[0210] (3) Self-healing performance test Test method: Use a scratch tester to scratch a 10-micron-wide scratch on the film surface and observe the repair status.

[0211] result: There is no obvious repair of scratches, and the self-healing rate is close to 0%.

[0212] Analysis: Traditional membranes lack a self-healing layer and are unable to repair damaged parts by themselves, which can easily lead to performance degradation.

[0213] (4) Durability test Test method: 10 stain-clean cycles were performed, each time staining with BSA solution and then cleaning with 0.1 wt% NaOH solution.

[0214] result: The water flux and salt retention rate dropped by about 30%, and the performance decayed seriously.

[0215] Analysis: After repeated contamination and cleaning, the performance of traditional membranes drops significantly, showing poor durability.

[0216] Table 2 Comparison table of comparative experimental data Embodiment 1 Traditional comparison Antifouling polymer membrane materials Polyethylene glycol none Nano self-healing particle materials Nano Silver none Water flux (L / m²·h) 250 280 Salt retention rate (%) 95 96 Antifouling performance (water flux reduction, %) <5 ≈25 Self-healing rate (%) >90 ≈0 Durability (performance retention after 10 cycles, %) >95 ≈70 By comparison, we can see that: Initial performance: Traditional membranes have slightly higher water flux and salt rejection in the initial stage, but lack anti-fouling and self-healing capabilities.

[0217] Anti-fouling performance: Example 1 has significant anti-fouling ability and stable performance during operation; traditional membranes are easily contaminated and their performance decreases rapidly.

[0218] Self-healing ability: Example 1 can self-repair micro-damage on the membrane surface and extend the service life of the membrane; traditional membranes cannot self-heal, and accumulated damage leads to performance degradation.

[0219] Durability: Example 1 has a high performance retention rate after long-term use and multiple cleanings; traditional membranes have poor durability and need to be replaced frequently, increasing operating costs.

[0220] Conclusion: Compared with the traditional method, the technical solution of the present invention significantly improves the anti-fouling performance, self-healing ability and durability of the reverse osmosis membrane, and has higher practical value and economic benefits.

[0221] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A new agent for efficiently repairing reverse osmosis membranes, comprising nano self-healing particles and anti-fouling polymers for constructing composite membranes, wherein the composite membranes comprise a base membrane layer, an anti-fouling polymer membrane layer and a nano self-healing layer, characterized in that : The nano self-healing particles are selected from nano silver or nano zinc oxide particles and are surface modified; The anti-fouling polymer material is selected from polyethylene glycol or polytetrafluoroethylene to form an anti-fouling layer with low surface energy.

2. The new agent for efficiently repairing reverse osmosis membrane according to claim 1 is characterized in that: The surface modification of the nano self-healing particles is carried out by using a silane coupling agent.

3. The new agent for efficiently repairing reverse osmosis membrane according to claim 1, characterized in that: The nano self-healing particles are temperature responsive or pH responsive, and include the following: The temperature responsiveness is achieved by incorporating a thermosensitive polymer into the particles; The pH responsiveness is achieved by incorporating pH sensitive materials into the particles.

4. The new agent for efficiently repairing reverse osmosis membrane according to claim 1, characterized in that: The thickness of the anti-fouling polymer film layer ranges from 5 to 10 micrometers, and the thickness of the nano self-healing layer ranges from 30 to 50 nanometers.

5. The new agent for efficiently repairing reverse osmosis membrane according to claim 1, characterized in that: The thickness of the base film layer ranges from 50 to 100 microns, and the base film layer is made of polyamide material and is formed by heat treatment at 100°C.

6. A process for preparing a novel agent for efficiently repairing reverse osmosis membranes, according to claim 1, wherein the novel agent for efficiently repairing reverse osmosis membranes is characterized in that: The following steps are involved: dissolving polyamide in N,N-dimethylformamide solvent to form a base film layer solution; Dissolving or dispersing polyethylene glycol or polytetrafluoroethylene to form an antifouling polymer solution, and coating the solution on the base film layer by dipping to form an antifouling film layer; The surface-modified nano self-healing particles are dispersed in ethanol or aqueous solution, a polyvinyl alcohol film-forming agent is added and coated on the anti-fouling film layer to form a nano self-healing layer.

7. The new preparation process of the high-efficiency agent for repairing reverse osmosis membrane according to claim 6 is characterized in that: The preparation steps of the base film layer include: The polyamide solution was evenly coated on the glass plate by knife coating; Pre-drying is performed at 40°C and heat treatment is performed at 100°C for 20 minutes to cure and form a base film layer.

8. The new preparation process of the high-efficiency agent for repairing reverse osmosis membrane according to claim 6 is characterized in that: The steps of preparing the antifouling polymer film layer include: The antifouling polymer solution was prepared by dispersing PTFE in ethanol by ultrasonic dispersion; The base film layer is immersed in the antifouling polymer solution for 3 to 5 minutes by dip coating, and UV curing or 80°C thermal curing is adopted to form an antifouling layer.

9. The new preparation process of the high-efficiency agent for repairing reverse osmosis membrane according to claim 6 is characterized in that: The preparation steps of the nano self-healing layer include: Performing surface modification treatment on nano silver or nano zinc oxide particles with a silane coupling agent to control the particle size to be between 20 and 30 nanometers; The modified nanoparticles are dispersed in ethanol or aqueous solution, and a polyvinyl alcohol film-forming agent is added, and the nanoparticles are coated on the antifouling polymer film layer by spin coating at a rate of 2000 rpm for 30 seconds.

10. The new preparation process of the high-efficiency agent for repairing reverse osmosis membrane according to claim 6 is characterized in that: After the nano self-healing layer is coated, it is low-temperature cured at 50°C for 30 minutes to allow the film-forming agent to stably adhere to the anti-fouling polymer film layer.